The authentic materials approach in the teaching of functional writing in the classroom - Maroko, Geoffrey Mokua (My University, 2010)
Students joining middle-level colleges, universities and the workplace have limited functional competency in English language. The teaching approaches and syllabi at institutions of learning do not give adequate attention to functional writing. The aim of this paper is to explore the authentic materials approach and demonstrate how it may be used in the teaching of functional writing in the classroom. The paper defines and classifies authentic materials, and explains how they apply to classroom functional writing. Second, it describes classroom authentic material analysis and evaluation activities that can be useful learning and teaching tools where the learners, as a result of reading and discussing, can go on to be effective functional text writers. Finally, the paper proposes an authentic text-based teaching and learning methodology that can be used in the acquisition of functional writing skills in the classroom.
Full text is available online at http://web.iess.ehime-u.ac.jp/raineruto2/5%20Geoffrey%20M%20Maroko.pdf